New Directions in Decompression Sickness Prevention – A Narrative Review - Ogorzałek, Filip Maciej; Zając, Maciej Tomasz; Rurkowska, Julia Emilia; Drelich, Krzysztof; Polczyk, Jakub Krzysztof; Rajzer, Przemysław; Golińska, Zofia; Deptuch, Wojciech; Szczuciński, Wiktor; Moćko, Paweł Krzysztof (Quality in Sport, 2026)
Background: Decompression sickness (DCS) is a serious medical condition that can develop in divers during ascent. It is associated with the formation of inert gas bubbles in blood vessels and tissues. Prevention is executed by performance of decompression stops to release nitrogen in a controlled manner, but as researchers highlight the role of complex inflammatory mechanisms and endothelial dysfunction, novel directions of prophylaxis in DCS are being explored. Objective: This narrative review synthesizes evidence on potential supplementary measures in DCS prevention, evaluating physical activity, biochemical and pharmacological interventions, as well as the impact of breathing mixtures usage. Methods: Evidence from clinical trials and animal studies was analyzed. Outcomes included biomarkers and parameters linked with DCS development, such as bubble grades, platelet depletion, microparticle (MP) accumulation and reduction of endothelial flow-mediated dilation (FMD). Results: Pre-dive aerobic exercise and usage of oxygen-enriched breathing mixtures consistently decrease venous gas emboli (VGE) formation. Ascorbic acid supplementation attenuates post-dive microparticle accumulation and mitigates reductions in FMD. In animal models, anti-thrombotic pretreatment with clopidogrel significantly decreases DCS mortality and platelet consumption, whereas aspirin and heparin show no protective effects. Conclusion: Pre-dive physical conditioning, specific antioxidant and anti-thrombotic pharmacological interventions, alongside enriched-oxygen breathing mixtures offer promising, complementary prophylactic measures to standard decompression protocols. Given the varying individual susceptibility to DCS, these alternative interventions provide a foundation for personalized diver safety protocols. Further large-scale clinical studies are necessary to establish optimal scopes of interventions and concrete guidelines for their implementation.